Association of social support, functional status, and psychological variables with changes in health‐related quality of life outcomes in patients with colorectal cancer. Issue 8 (18th November 2015) - Gonzalez‐Saenz de Tejada, M.; Bilbao, A.; Baré, M.; Briones, E.; Sarasqueta, C.; Quintana, J.M.; Escobar, A.
Abstract: Background: The aim of this study was to explore the association of social support received, and functional and psychological status of colorectal cancer patients before surgery with changes in health‐related quality of life (HRQoL) outcomes measured by EORTC QLQ‐C30 at 1‐year post‐intervention. Methods: Consecutive patients that were because of undergo therapeutic surgery for the first time for colon or rectum cancer in nine hospitals in Spain were eligible for the study. Patients completed questionnaires before surgery and 12 months afterwards: one HRQoL instrument, the EORTC QLQ‐C30; a social network and social support questionnaire, the Duke‐UNC Functional Social Support Questionnaire; the Hospital Anxiety and Depression Scale, to assess anxiety and depression; and the Barthel Index, to assess functional status; as well as questions about sociodemographic information. General linear models were built to explore the association of social support, functional status, and psychological variables with changes in HRQoL 12 months after intervention. Results: A total of 972 patients with colorectal cancer took part in the study. Patients' functional status, social support, and anxiety and depression were associated with changes in at least one HRQoL domain. The higher functional status, and the higher social support, the more they improved in HRQoL domains. Regarding anxiety and depression, the more anxiety and depression patients have at baseline, less they improve in HRQoL domains. Conclusions: Patients with colorectal cancer who have more social support and no psychological distress may have better results in HRQoL domains at 1 year after surgery. Copyright © 2015 John Wiley & Sons, Ltd.